Targeting PCSK9 Ameliorates Graft Vascular Disease in Mice by Inhibiting NLRP3 Inflammasome Activation in Vascular Smooth Muscle Cells - Zou, Yanqiang; Chen, Zhang; Zhang, Xi; Yu, Jizhang; Xu, Heng; Cui, Jikai; Li, Yuan; Niu, Yuqing; Zhou, Cheng; Xia, Jiahong; Wu, Jie (Frontiers in Immunology, 2022)
Background Graft vascular disease (GVD), which limits the long-term survival of patients after solid-organ transplantation, is associated with both immune responses and nonimmune factors, including dyslipidemia. Recent studies have shown that inhibition of proprotein convertase subtilisin/kexin type 9 (PCSK9), a U.S. Federal Drug Administration-approved treatment for hyperlipidemia, reduces cardiovascular events, regulates inflammatory responses, and enhances the efficacy of immune checkpoint therapy in cancer treatment through a cholesterol-independent mechanism. However, whether targeting PCSK9 is a potential therapeutic strategy for GVD remains unknown. Methods Serum samples and grafts were harvested from male mice undergoing abdominal aortic transplantation. The pathological alterations in the aortic grafts were detected by hematoxylin and eosin staining, Verhoeff’s Van Gieson staining, and Masson staining. Inflammatory cell infiltration and proinflammatory cytokine expression in the aortic grafts were detected by immunohistochemistry and quantitative real-time polymerase chain reaction (qRT-PCR), respectively. The regulatory effects of PCSK9 on vascular smooth muscle cell (VSMC) migration and proliferation were examined by transwell, EdU, and western blot assays. The effect of Evolocumab, a PCSK9 inhibitor, on GVD in humanized PCSK9 mice was also evaluated. Results PCSK9 was upregulated in the serum, grafts, and liver of mice in the allograft group subjected to abdominal aortic transplantation. Pcsk9 knockout significantly reduced vascular stenosis, the intimal hyperplasia area and collagen deposition. Pcsk9 depletion also inhibited macrophage recruitment and the mRNA expression of proinflammatory cytokines in aortic grafts. Furthermore, Pcsk9 knockout suppressed the migration and proliferation of VSMCs, which was related to the inhibition of NLRP3 inflammasome activation. Meanwhile, Evolocumab significantly ameliorated GVD in humanized PCSK9 mice. Conclusion PCSK9 is upregulated in a mouse model of GVD, and Pcsk9 knockout reduces vascular occlusion, suggesting that PCSK9 may be a promising target for the treatment of GVD.